Advances in digital light processing of hydrogels. (1st July 2022) - Mo, Xingwu; Ouyang, Liliang; Xiong, Zhuo; Zhang, Ting
Abstract: Hydrogels, three-dimensional (3D) networks of hydrophilic polymers formed in water, are a significant type of soft matter used in fundamental and applied sciences. Hydrogels are of particular interest for biomedical applications, owing to their soft elasticity and good biocompatibility. However, the high water content and soft nature of hydrogels often make it difficult to process them into desirable solid forms. The development of 3D printing (3DP) technologies has provided opportunities for the manufacturing of hydrogels, by adopting a freeform fabrication method. Owing to its high printing speed and resolution, vat photopolymerization 3DP has recently attracted considerable interest for hydrogel fabrication, with digital light processing (DLP) becoming a widespread representative technique. Whilst acknowledging that other types of vat photopolymerization 3DP have also been applied for this purpose, we here only focus on DLP and its derivatives. In this review, we first comprehensively outline the most recent advances in both materials and fabrication, including the adaptation of novel hydrogel systems and advances in processing (e.g. volumetric printing and multimaterial integration). Secondly, we summarize the applications of hydrogel DLP, including regenerative medicine, functional microdevices, and soft robotics. To the best of our knowledge, this is the first time that either of these specific review focuses has been adopted in the literature. More importantly, we discuss the major challenges associated with hydrogel DLP and provide our perspectives on future trends. To summarize, this review aims to aid and inspire other researchers investigatng DLP, photocurable hydrogels, and the research fields related to them.